Role Of Social Media In Learning English As Foreign Language: An Exploratory Study At Post Graduate Level - Dr. Syeda Naureen Mumtaz , Dr. Fakhra Aziz , Dr. Moafia Nader , Ms Alishba Rashid (Migration Letters, 2024)
English language is recognized as the global language and is used across diverse fields. It is taught as one of the compulsory subjects started from primary education to intermediate level across Pakistan. It also serves as the medium of instruction in Pakistani educational system. Therefore, the present study aims to investigate the impact of social media on enhancing English language understanding and its proficiency among university students in the Lahore District. The objectives are to assess university-level learners’ access to and use of various social media platfor[1]ms for improving English language precisely its listening and speaking skills at the postgraduate level. The research design employed was descriptive and quantitative, by method, aligning with a post-positivist philosophical paradigm. The population for this study consisted of universities in the Lahore district, and for the selection of sample convenience sampling technique was used. Utilizing cluster sampling, two universities Superior University and University of Central Punjab were chosen due to time and resource constraints. The data collection instrument is questionnaire. Data was collected personally by the researcher by using a five-point Likert Scale. IBM SPSS version 26.0 was utilized for data analysis. The findings provide valuable insights into the role of social media in language education and its improvement among University level students. The study indicates that students spend significant time on social media for English language earning. The study recommends to emphasize the need for educators to inform students of the advantages of utilizing social media to improve their understanding and proficiency in English language at the university level.